Electrokinetic energy conversion of two-layer fluids through nanofluidic channels. (29th January 2019) - Ding, Zhaodong; Jian, Yongjun; Tan, Wenchang
Abstract : Based on the Onsager reciprocal relation in the linear response regime, we first clarify the equivalence of thermodynamic and electric circuit analyses for electrokinetic energy conversion. Then we present a streaming-potential-based nanofluidic energy conversion system which comprises two immiscible fluids that form a flat interface in a slit-like channel. The validity of the Onsager reciprocal relation to such a two-fluid system is verified. The performance of such an energy converter is illustrated by considering two concrete oil–water systems with different properties. In both cases, we predict that the binary system with a thin oil layer increases both the maximum output power and the energy conversion efficiency, and this enhancement depends strongly on the mobile charges present at the oil–water interface, the salt concentration and the interface location. Concretely, for negatively charged interfaces, we find that the optimal efficiency increases with the interfacial charge for relatively thin oil layers; while for relatively thick oil layers, the interfacial charge has the opposite effect (i.e. reduction effect) on the energy conversion efficiency in the ranges of the parameters. We further investigate these systems from the viewpoint of energy transfer by deriving the related energy equation. We find that viscous dissipation consumes most of the power (more than 90 %), in both single-phase and two-fluid flows. However, the ratio of the viscous dissipation to the power input decreases with increase of the interfacial charge density for the case of a relatively thin oil layer in two-fluid flows. Meanwhile, although the presence of interfacial charges can lead to an increase in electrical dissipation, the amount of the increased power consumption is less than that of the reduced viscous dissipation in the case of a thin oil layer. Therefore, for two-fluid energy converters, the total power consumption can be reduced and the efficiency is improved.